Entrepreneurial risk allocation in public-private infrastructure provision in South Africa - F. Ahwireng-Obeng; J. P. Mokgohlwa (South African Journal of Business Management, 2002)
A primary concern in the development of entrepreneurship through private-public partnerships (PPP) in infrastructure projects is the adversarial, complex and unequal power relations characterising the negotiation of project risk allocation (RA) among the multiple participants. The inertia of the RA process has led to delayed and costly financial closure and sub-economic costs. Transactions costs of up to ten percent have been incurred in documented cases, and the situation is exacerbated in emerging economies, like South Africa, by political and economic instability and unproven track record of PPP. These developments have led to frustration among private sector participants in PPPs and diminished incentives for their continued participation. Therefore, delivering “satisfactory” RA processes is critical for attracting both domestic and foreign private entrepreneurial resources. The aim of this paper was to ascertain ‘critical factors’ influencing RA processes; determine the extent to which PPP practices in South Africa have led to equitable entrepreneurial risk allocation; and assess the choice of contract for implementing the outcomes of PPP negotiations. Critical success factors included: limiting apprehensions about market, socio-political, regulatory and legal risks as well as risk of lenders; improving common understanding among PPP participants; enhancing the quality of RFP (request for proposal) processes; and strengthening the commitment of participants. RA practices regarding socio-political, regulatory, financial and legal risks allocations were found to be inequitable, and PPP participants preferred tight and highly specified contracts.